We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
358
2
avatar

how do you solve this? 5(2x-6)=3x-2

 Aug 19, 2015

Best Answer 

 #2
avatar
+5

$${\mathtt{5}}{\mathtt{\,\times\,}}\left({\mathtt{2}}{\mathtt{\,\times\,}}{\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{6}}\right) = {\mathtt{3}}{\mathtt{\,\times\,}}{\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{2}} \Rightarrow {\mathtt{x}} = {\mathtt{4}}$$

Angelo

 Aug 19, 2015
 #1
avatar+17776 
+5

5(2x - 6)  =  3x - 2

First: remove parentheses:

10x - 30  =  3x - 2

Then:  get all the x-terms to one side; subtract 3x from both sides:

7x - 30  =  -2

Now:  get all the numbers to the other side; add 30 to both sides:

7x  =  28

Finally, divide both sides 7:

x  =  4

 Aug 19, 2015
 #2
avatar
+5
Best Answer

$${\mathtt{5}}{\mathtt{\,\times\,}}\left({\mathtt{2}}{\mathtt{\,\times\,}}{\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{6}}\right) = {\mathtt{3}}{\mathtt{\,\times\,}}{\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{2}} \Rightarrow {\mathtt{x}} = {\mathtt{4}}$$

Angelo

Guest Aug 19, 2015

4 Online Users